2019
DOI: 10.1093/ofid/ofz379
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Transplant in Children With Clostridioides difficile Gives Sustained Reduction in Antimicrobial Resistance and Potential Pathogen Burden

Abstract: Background Fecal microbiota transplantation (FMT) treats Clostridioides difficile infection (CDI). Little is known regarding the changes in antimicrobial resistance (AMR) genes and potential pathogen burden that occur in pediatric recipients of FMT. The aim of this study was to investigate changes in AMR genes, potential pathogens, species, and functional pathways with FMT in children. Methods Nine children with recurrent CDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 63 publications
4
43
0
Order By: Relevance
“…After FMT, the levels of F. prausnitzii were significantly increased at week 4 compared with the baseline, but remained lower compared with healthy donors. F. prausnitzii abundance is strongly correlated with the diagnostic and therapeutic effectiveness of FMT (54).…”
Section: Discussionmentioning
confidence: 99%
“…After FMT, the levels of F. prausnitzii were significantly increased at week 4 compared with the baseline, but remained lower compared with healthy donors. F. prausnitzii abundance is strongly correlated with the diagnostic and therapeutic effectiveness of FMT (54).…”
Section: Discussionmentioning
confidence: 99%
“…Solving such technical challenges could help us to understand better the role of bacteriophages in microbiome ecology. This is therapeutically important: bacteriophage transfer during FMT and abiotic FMT was associated with a positive outcome in patients with recurrent C. difficile infection [74][75][76], highlighting the complex interkingdom interactions within the microbiota community. down to specific microbes, such as when a specific commensal belonging to the Bifidobacterium genus promotes antitumor immunity in mice [24].…”
Section: Oncogenic Viruses and The Microbiomementioning
confidence: 99%
“…A meta-analysis including both adults and children patients did not demonstrate any significant differences in outcomes when comparing FMT for rCDI via colonoscopy versus the NG tube [45]. In a multicentre study, FMT using colonoscopy was found to be significantly more effective than FMT delivered using other routes in children [46].…”
Section: Recurrences and Faecal Microbiota Transplant (Fmt)mentioning
confidence: 88%
“…Table 3 summarizes antimicrobial treatment suggested for recurrent CDI in the paediatric population [19]. Good clinical response with FMT has been observed in adults with refractory or recurrent CDI with few reports of adverse events [44][45][46]. At present, data examining the effectiveness of FMT for children are lacking.…”
Section: Recurrences and Faecal Microbiota Transplant (Fmt)mentioning
confidence: 99%
See 1 more Smart Citation